Preparation of Financial Statements in Accordance with SAK EMKM in the UD Restu Jaya Cracker Business, Puger District, Jember Regency - Atika Puspita Sari; Yulinartati Yulinartati; Ibna Kamilia Fiel Afroh (Westscience Press, 2024)
This study aims to analyze the application of financial accounting standards for micro, small and medium entities (SAK EMKM) at UD Restu Jaya Puger. This research was conducted on MSMEs engaged in production, namely cracker production. This research uses a qualitative method with a type of descriptive approach. This research was carried out by obtaining data through observation, interviews and documentation. The results of this study show that UD Restu Jaya in its financial records is still manual and simple, because the owner has not understood how to prepare financial statements in accordance with SAK EMKM and there has been no socialization received related to the SAK EMKM that has been determined. This research is expected to provide information for MSME owners in implementing financial statements in accordance with SAK EMKM.